Can digital technology reduce carbon emissions? Evidence from Chinese cities - Liu, Hui; Wang, Lili; Shen, Yang (Frontiers in Ecology and Evolution, 2023)
Global warming presents significant challenges to the sustainable development of human society.Accelerating the achievement of carbon peak and neutrality is the vision for creating a global ecological community with a shared future. The development of digital technology provides us with the direction of action. Based on panel data from 276 cities in China from 2011 to 2020, this paper used a two-way fixed effects model and instrumental variable method to verify the impact of digital technology on carbon emissions from the perspective of technology diffusion. The results show that the deep diffusion of digital technology in the real economy sector is helpful to improve productivity and carbon efficiency, thus significantly reducing carbon emissions, especially in large cities, resource-based cities, smart cities and pilot areas of carbon emission trading policies. Digital technology can reduce carbon emissions by improving energy efficiency, promoting green technology innovation, and promoting virtual agglomeration. The contribution of this paper is that it not only reveals that digital technology can reduce carbon emissions but also analyzes the emission reduction path of digital technology from a new perspective. The conclusion of this paper has implications for accelerating the diffusion of digital technology in the real economy sector to accelerate the realization of green production and cope with climate change.